Multimeric Presentation of RGD Peptidomimetics Enhances Integrin Binding and Tumor Cell Uptake. Issue 33 (19th May 2020) - Pina, Arianna; Kadri, Malika; Arosio, Daniela; Dal Corso, Alberto; Coll, Jean‐Luc; Gennari, Cesare; Boturyn, Didier
Abstract: The use of multimeric ligands is considered as a promising strategy to improve tumor targeting for diagnosis and therapy. Herein, tetrameric RGD (Arg‐Gly‐Asp) peptidomimetics were designed to target αv β3 integrin‐expressing tumor cells. These compounds were prepared by an oxime chemoselective assembly of cyclo (DKP‐RGD) ligands and a cyclodecapeptide scaffold, which allows a tetrameric presentation. The resulting tetrameric RGD peptidomimetics were shown to improve αv β3 integrin binding compared with the monomeric form. Interestingly, these compounds were also able to enhance tumor cell endocytosis in the same way as tetrameric RGD peptides. Altogether, the results show the potential of the tetrameric cyclo (DKP‐RGD) ligands for in vivo imaging and drug delivery. Abstract : Multiplicity makes for strength : Multimeric presentation can effectively increase the strength of peptidomimetic ligand–receptor interactions and enhance tumor cell uptake.